Transmissibility and Infection Control Implications of Burkolderia cepacia in Cystic Fibrosis. (1st June 1998) - Fung, Scott K; Dick, H; Devlin, H; Tullis, E
Abstract : OBJECTIVE: To describe the microbiology and potential virulence factors of Burkholderia cepacia ; to discuss the studies that have investigated its mode of transmission among cystic fibrosis patients; and to identify the major risk factors associated with acquisition of this pathogen inside and outside of the hospital environment. DATA SOURCES: MEDLINE search of the literature published between 1986 and 1997 using the key words/subject words Pseudomonas cepacia, Burkholderia cepacia, cystic fibrosis, infection control and transmissibility, and the bibliography of selected papers. DATA EXTRACTION: Selected studies examining epidemiology, microbiology, virulence factors and mode of transmission of B cepacia in cystic fibrosis. DATA SYNTHESIS AND CONCLUSIONS: B cepacia is a multidrug-resistant Gram-negative bacillus that has recently been recognized as a major respiratory pathogen in patients with cystic fibrosis. Colonization by this organism can lead to rapid pulmonary deterioration and premature death. Recent studies based on genomic subtyping techniques have suggested that it can be transmitted from person to person. Close social contact and hospitalization have been identified as risk factors for cross-infection. With the implementation of strict infection control policies such as segregation according to colonization status, the rate of new colonization has substantially decreased in most cystic fibrosis treatment centres.